Ni modified distillation waste derived heterogeneous catalyst utilized for the production of glycerol carbonate from a biodiesel by-product glycerol: Optimization and green metric studies - Jaiswal S.; Sharma Y.C. (My University, 2025)
Biodiesel prices could be made competitive with petrol-diesel prices by valorizing its by-product glycerol. Glycerol carbonate can be derived from glycerol and is one of the widely needed chemical having high price and its extensive application in different industrial purposes. Glycerol carbonate can be synthesized via many routes; among them catalytic route gives promising activity and selectivity towards glycerol carbonate. For the first time, Ni modified distillation waste (CaO) derived heterogeneous catalyst Ni/CaO (NDW) was synthesized and utilized for the conversion of glycerol (Gl) to glycerol carbonate (GC). The catalyst's physicochemical properties were studied by performing TGA-DSC, XRD, FT-IR, SEM- EDAX, HRTEM, and basicity through Hammet indicator. Through NDW, solvent-free synthesis of glycerol carbonate was achieved using glycerol and dimethyl carbonate (DMC) as reactants upon conventional heating (90 °C). The validation of the synthesized product was performed through proton and carbon NMR analysis. In addition to this, HR-MS was performed to check the composition of the product formed. A plausible mechanism for the transesterification of glycerol (Gl) to glycerol carbonate (GC) was also designed. Higher conversion (99.2%) and selectivity (95%) towards glycerol carbonate (GC) were achieved at mild reaction conditions, viz., 1:3 M ratio of glycerol to DMC, reaction temperature 90 °C, reaction duration of 90 min with catalyst dose of 300 mg. The green metric parameters were also calculated to show that the overall process is sustainable and the environment benign. © 2022